2022
DOI: 10.3389/fimmu.2022.968778
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of clonal hematopoiesis of indeterminate potential in hospitalized patients with COVID-19

Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) leads to higher mortality, carries a cardiovascular risk and alters inflammation. All three aspects harbor overlaps with the clinical manifestation of COVID-19. This study aimed to identify the impact of CHIP on COVID-19 pathophysiology. 90 hospitalized patients were analyzed for CHIP. In addition, their disease course and outcome were evaluated. With a prevalence of 37.8%, the frequency of a CHIP-driver mutation was significantly higher than the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Table S4: Clonal Hematopoiesis of Indeterminate Potential (CHIP) Genes and DNA methylation (DNAm) Genes CHIP genes were compiled from Schenz et al 27 and Hagiwara et al 34 DNAm genes were compiled from Rasmussen & Helin 57 and Ginno et al 58 These genes were used for our analysis of CHIP genes and DNAm gene variants respectively.…”
Section: Table S3: Sequencing Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Table S4: Clonal Hematopoiesis of Indeterminate Potential (CHIP) Genes and DNA methylation (DNAm) Genes CHIP genes were compiled from Schenz et al 27 and Hagiwara et al 34 DNAm genes were compiled from Rasmussen & Helin 57 and Ginno et al 58 These genes were used for our analysis of CHIP genes and DNAm gene variants respectively.…”
Section: Table S3: Sequencing Coveragementioning
confidence: 99%
“…Clonal hematopoiesis of indeterminate potential (CHIP) is characterized by somatic mutations in leukemia-related “CHIP” genes detected in the blood of individuals without apparent hematologic malignancy 26,27 . The definition of CHIP has been a subject of ongoing discussion, ranging from a benign precursor state for hematologic neoplasms 28 , to the presence of a clonally expanded hematopoietic stem cell with a mutation with leukemogenic potential 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al (60) observed a unique IFN-γ signature in severe COVID-19 patients with CH, which was partly explained by CH-dependent epigenetic alterations in classical (proinflammatory) monocytes. Furthermore, Schenz et al (61) provide evidence that CH exacerbates lymphoid and myeloid alterations in severe COVID-19. They found these associations to be age-dependent, as CH-associated lymphoid alterations were more prominent among individuals under 60 years old, whereas myeloid alterations were enhanced in the above-60 age group with CH (61).…”
Section: Clonal Hematopoiesis May Influence Inflammation In Covid-19mentioning
confidence: 99%
“…Furthermore, Schenz et al (61) provide evidence that CH exacerbates lymphoid and myeloid alterations in severe COVID-19. They found these associations to be age-dependent, as CH-associated lymphoid alterations were more prominent among individuals under 60 years old, whereas myeloid alterations were enhanced in the above-60 age group with CH (61). Whether these effects influence COVID-19 outcomes has yet to be determined, but based on these observations, further exploration is warranted.…”
Section: Clonal Hematopoiesis May Influence Inflammation In Covid-19mentioning
confidence: 99%
“…By estimating the timing of clone initiation and subsequent growth rates of clones, we can characterize evolutionary mechanisms that underlie aging 8 and malignant progression [9][10][11][12] . In blood, for example, this evolutionary process is known as clonal hematopoiesis and has been associated with many aging-related disorders such as anemia 13 , impaired immunity 14,15 , and cardiovascular disease 16,17 , as well as progression to hematopoietic cancers 5,9,18 . Previous analyses found that somatic mutations conferring higher fitness, measured by clonal growth rate, lead to a higher risk of malignant transformation [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%